Restructured Fish Nuggets from ‘Wallago Attu’ Extended with Soy Protein Isolate - Biswas, Olipriya; Das, Sudip Kumar; Biswas, S. (Journal of Meat Science, 2016)
The present study was conducted to prepare restructured fish nuggets from comparatively low-value cuts of ‘Wallago attu’ (Boal), with incorporation of soy protein isolate at different levels viz. 2.5% (T1), 5% (T2) and 7.5% (T3). Physicochemical, microbiological and sensory qualities were estimated on 0, 3, 7 and 14 days of refrigerated storage. Cooking yield (%) and Water Holding Capacity (WHC) were found to be significantly higher (p<0.05) in T3 group (89.31± 1.28 and 45. 72 ±0.79 respectively) in 0 day, when compared to control group which had a cooking yield and WHC of 83.14 ± 0.67 and 40.11 ± 0.76 respectively on 0 day. Moisture content differences between the treatments were significant (p<0.05). Highest moisture % observed in T3 group (82.54 ± 1.51), whereas lowest in control group (75.12 ± 0.76) on 0 day. pH values were not affected (p>0.05) by treatment but decreased significantly (p<0.05) with the progress of storage. However, beyond 7th day, it showed a significant (p<0.05) increasing trend. Thio-barbituric acid (TBA) value, peroxide value, free fatty acids and total plate counts exhibited significant (p<0.05) increasing trend with the storage period and significant decreasing trend (p<0.05) with increase in level of incorporation. Soy protein isolate up to 7.5% increased the sensory acceptability of the nuggets throughout the storage period. However, within a treatment group, sensory scores deteriorated significantly (p<0.05) with the advancement of storage period. Based on the results, nuggets containing 7.5% SPI are recommended for the preparation of cost effective fish nuggets.